2006
DOI: 10.1542/peds.2005-1837
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-Disordered Breathing, Behavior, and Cognition in Children Before and After Adenotonsillectomy

Abstract: Objectives: Most children with sleep-disordered breathing (SDB) have mild to moderate forms, for which neurobehavioral complications are believed to be the most important adverse outcomes. To improve understanding of this morbidity, its long-term response to adenotonsillectomy, and its relationship to polysomnographic measures, we studied a series of children before and after clinically-indicated adenotonsillectomy or unrelated surgical care.Methods: We recorded sleep and assessed behavioral, cognitive, and ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
265
1
13

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 411 publications
(295 citation statements)
references
References 44 publications
9
265
1
13
Order By: Relevance
“…[22][23][24][25][26][27][28][29][30] The plausibility of the obstructive sleep apnea syndrome contributing to cognitive deficits is supported by research showing impaired learning in juvenile rats exposed to intermittent hypoxemia 3 and by imaging studies showing cerebral neuronal injury in children with the syndrome. 30 Previous studies have shown differences in the cognitive function of children with the obstructive sleep apnea syndrome, as compared with controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[22][23][24][25][26][27][28][29][30] The plausibility of the obstructive sleep apnea syndrome contributing to cognitive deficits is supported by research showing impaired learning in juvenile rats exposed to intermittent hypoxemia 3 and by imaging studies showing cerebral neuronal injury in children with the syndrome. 30 Previous studies have shown differences in the cognitive function of children with the obstructive sleep apnea syndrome, as compared with controls.…”
Section: Discussionmentioning
confidence: 99%
“…19,27,31 However, baseline cognitive scores of children with the obstructive sleep apnea syndrome fell within the normal range, a finding similar to that in the current study. Cognitive and behavioral abnormalities have been shown to be reduced after adenotonsillectomy in some, [24][25][26][27]29 but not all, 30 nonrandomized studies, with inconsistency in the reported effect after treatment. 25,29,32 Previous studies have been limited by small samples, lack of randomization or appropriate controls, heterogeneous study groups, and sole reliance on parent questionnaires rather than including neuropsychological testing.…”
Section: Discussionmentioning
confidence: 99%
“…(6)(7)(8)(9)(10)(11)(12) Identification of children at high risk for SDB and its associated morbidities is particularly important given the growing body of evidence that treatment with adenotonsillectomy may improve quality of life and neurocognitive function. (5,(13)(14)(15)(16)(17) Preterm infants are especially vulnerable both to SDB and its sequelae. In a Finnish cohort study, very low birth weight infants were shown to have a two-fold risk of SDB as young adults.…”
mentioning
confidence: 99%
“…Studies have identified and reported post-therapy AHI and/or oxygen saturation and other respiratory measures, sleep EEG analysis such as sleep stages, spindles, arousals, and spectral analysis, various neurocognitive and/or behavioral measures, parental and teacher report of improvement or satisfaction, academic performance, and more recently serologic markers [5][6][7][8] such as C-Reactive Protein, and other physiological tests [7,9] as evidence of treatment effect. Interestingly, these outcomes do not necessarily show symmetry at baseline or in response to intervention ; for example, in children treated by adenotonsillectomy, hyperactivity, inattention, cognitive function, and other neurobehavioral morbidities all tended to be improved a year after treatment, but little correlation has been seen between some of these variables and polysomnographic measures before or after surgery, though esophageal pressure monitoring as a more sensitive measure of breathing abnormalities may offer some promise in this regard [10,11].…”
Section: Sleep Disordered Breathingmentioning
confidence: 99%
“…Smaller or uncontrolled studies suggest that adenotonsillectomy may improve OSA-related deficits in attention, memory, performance, and/ or behavior [10,11,24,25]. The Childhood Adenotonsillectomy Trial (CHAT) was recently undertaken to assess neuropsychological and health outcomes in children randomized to receive early AT (eAT) as compared to Watchful Waiting with Supportive Care (WWSC) [18].…”
Section: Sleep Disordered Breathingmentioning
confidence: 99%